Procalcitonin levels predict infectious complications and response to treatment in patients undergoing cytoreductive surgery for peritoneal malignancy. Issue 2 (February 2016) - Saeed, K.; Dale, A.P.; Leung, E.; Cusack, T.; Mohamed, F.; Lockyer, G.; Arnaudov, S.; Wade, A.; Moran, B.; Lewis, G.; Dryden, M.; Cecil, T.; et al.
Abstract: Background: Cytoreductive-surgery for peritoneal-malignancy (PM) involves extensive intra-abdominal surgery and a massive post-operative systemic–inflammatory-response (SIRS). It is often challenging to differentiate SIRS that are solely surgery-associated from those of post-operative infections. White-Cell-Counts (WCC) and C-Reactive-Protein (CRP) are routinely used as markers for infection, but are non-specific and their elevation is often delayed in PM cases. Other markers need to be evaluated to assist early identification/prediction of post-operative infections. Methodology: Prospective evaluation of serum procalcitonin (PCT), CRP and WCC in 50 patients pre-operatively (Day0), and on post-operative days (POD) 1, 3 & 6, following cytoreductive-surgery with or without splenectomy. Results: Day0 PCT, CRP and WCC values were within normal limits, but increasing physiologically in post-operative period without infection, with noticeable higher PCT in splenectomized patients. In our cohort post-operative infections were diagnosed in 14 patients, often within 48 h. There was a trend for faster rise in serum PCT on POD1 compared to CRP and WCC, and faster PCT decline following appropriate therapy on POD3 and POD6 when infected cases were clinically resolving while WCC and CRP continued to rise, particularly in non-spelenectomised patients. The AUC on POD1 was significantly higher for PCT (0.689) vs. WCC (0.476) and CRP (0.477) ( p = 0.04). Sensitivity, specificity, positive-predictive-value and negative-predictive-values for PCT ranged between (57%–100%), (22%–74%), (33%–47%) & (81%–100%), for CRP (28%–78%), (5.5%–86%), (18%–44.4%) & (40%–75.5%) and for WCC (14%–26.5%), (65.5–80.5%), (22%–25%), (67%–70%) respectively. Conclusion: PCT, like WCC and CRP, needs to be interpreted with extreme cautions in the context of infections post-cytoreductive-surgery and should only be used in association with other clinical and investigational findings.